Effects of renin-angiotensin system inhibitor and beta-blocker use on mortality in older patients with heart failure with reduced ejection fraction in Japan - Kawada, Kei; Ishida, Tomoaki; Fukuda, Hitoshi; Hyohdoh, Yuki; Kubo, Toru; Hamada, Tomoyuki; Baba, Yuichi; Hayashi, Toshinobu; Aizawa, Fuka; Yagi, Kenta; Izawa-Ishizawa, Yuki; Niimura, Takahiro; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Guideline-directed medical therapy with renin-angiotensin system (RAS) inhibitors and beta-blockers has improved the survival of patients with heart failure (HF) and reduced left ventricular ejection fraction (HFrEF). However, it is unclear whether RAS inhibitors and betablockers can be administered to older patients with HF. Therefore, this study aimed to investigate the effects of beta-blockers and RAS inhibitors on the prognosis of older patients with HFrEF. Methods Demographic, clinical, and pharmacological data from 1,061 patients with acute decompensated HF, enrolled in the Kochi Registry of Subjects with Acute Decompensated Heart Failure (Kochi YOSACOI study), were analyzed to assess their impact on mortality. Additionally, a machine learning approach was applied to complement the conventional statistical model for analysis. Patients with HFrEF (n = 314) were divided into the all-cause mortality within 2 years group (n = 80) and the survivor group (n = 234).Results Overall, 41.1% (129/314) of the patients were aged ≥80, and 25.5% (80/314) experienced all-cause mortality within 2 years. Furthermore, 57.6% (181/314) and 79.0% (248/314) were prescribed RAS inhibitors and beta-blockers, respectively. Our analysis showed that RAS inhibitor use was associated with reduced all-cause mortality and cardiac death in patients with HFrEF of all ages (P < 0.001), and beta-blocker use had an interaction with age. Machine learning revealed that the use of beta-blockers altered the risk of mortality, with a threshold of approximately 80 years of age. Beta-blocker use was associated with lower all-cause mortality and cardiac death in patients with HFrEF aged <80 years (P<0.001) but not in those aged ≥80 years (P = 0.319 and P = 0.246, respectively). These results suggest that beta blockers may differ in their all-cause mortality benefits according to age.Conclusions RAS inhibitors prevented all-cause mortality and cardiac death at all ages, whereas beta-blockers had different effects depending on the patient's age. This study suggested that the choice of beta-blockers and RAS inhibitors is more important in older patients with HFrEF than in younger patients with the same condition.